Penerapan Model Student Active Learning untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Tematik SD Kota Bengkulu - Zanaidah, Ristini; Anggraini, Dwi (Universitas Bengkulu, 2025)
This consider points to portray the usage of the application of the understudy dynamic learning demonstrate and analyze understudy learning results in topical learning (PTK Course III SD N 02 Bengkulu City). The investigate strategy utilized is classroom activity inquire about (PTK) with investigate disobedient, specifically the usage perception sheet and developmental assessment test carried out in two cycles with the Kemmis and Taggart cycle utilizing 4 stages, specifically arranging, activity, perception, reflection. The inquire about subjects were third review understudies of SDN 02 Bengkulu City totaling 29 understudies comprising of 15 female understudies and 14 male understudies. The comes about of the consider expressed that there was an increment within the execution of the application of the SAL show, this may be seen from the increment within the normal procurement of the usage of the SAL show in cycle I gotten a score of 25 expanding to 33.5 with a great category in cycle II. At that point the learning results are prove by the normal esteem and rate of understudy learning within the frame of cognitive. Cycle I learning results in Indonesian subjects learning completeness was 34%, with an normal of 52.7, Arithmetic subjects learning completeness was 58% with an normal of 65.8 and SBDP subjects with learning completeness of 62% and an normal of 68.2. So, it is concluded that the application of the Understudy Dynamic Learning Demonstrate can move forward understudy learning results in topical learning (PTK lesson III SDN 02 Bengkulu City). The conclusion gotten by applying the Understudy Dynamic Learning show in review III SD can move forward the usage of the SAL show and topical learning results.